Closing the Potential-Performance Divide in Ugandan Agriculture - World Bank Group (World Bank, Washington, DC, 2018)
Agriculture accounts for 70 percent of employment, overwhelmingly on small farms; occupies half of all land area, and provides half of all exports and one-quarter of GDP in Uganda. It is considered a leading sector for future economic growth and economic inclusion in the current National Development Plan. Yet despite having very favorable natural resource and climate conditions for production of a wide variety of crops and livestock, average Total Factor Productivity (TFP) growth--the difference between aggregate output growth and the growth of all inputs and factors of production that produced it--in Ugandan agriculture has been negative for the last two decades. This suggests that on balance the country is now getting less for equal or greater effort. While drought and pest issues likely have played a harmful role, other plausible explanations are a combination of the following: weakening over time of the public institutional base for promoting agricultural productivity at the level of small farms, inefficiencies in agricultural public expenditures, inadequate agricultural regulation and policies, and a lack of collateralizable farm assets. National agricultural output has grown at only 2 percent per annum over the last five years, compared to agricultural output growth of 3 to 5 percent in other EAC members and 3.3 percent per annum growth in Uganda's population over the same period.